Cerebral Amyloid Angiopathy Related Inflammation With Prominent Meningeal Involvement. A Report of 2 Cases - Agnès Aghetti; Agnès Aghetti; Damien Sène; Damien Sène; Marc Polivka; Natalia Shor; Sarah Lechtman; Sarah Lechtman; Hugues Chabriat; Hugues Chabriat; Hugues Chabriat; Eric Jouvent; et al. (Frontiers in Neurology, 2019)
Cerebral amyloid angiopathy related inflammation (CAA-RI) is a rare form of CAA characterized by subacute encephalitic symptoms (cognitive decline, seizures, focal deficits) associated with extensive and confluent white matter lesions co-localizing with lobar microbleeds on brain MRI. We report two cases of unusual CAA-RI mimicking meningoencephalitis but without typical brain lesions on FLAIR and T2* sequences. These 2 cases may extend the clinical spectrum of CAA-RI by suggesting the possible occurrence of quite purely meningeal forms of CAA-RI.